IMPLEMENTASI SIMULATOR DETAK JANTUNG PADA ALAS TIDUR BAYI - , YOSSAFAT REINAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
It is known that audible relaxation could increase the comfort of the infant. The fact of mother's heart helps to relax an infant made a thougt simulating the sound of the human heart. Heartbeat simulator system is hoped could increase the relaxation of the infant during the sleep activity. In this research, simulator system use baby detection in the form of photodiode and infra red led. The baby detection enable system just run if there is a baby on the baby sleeping bed. System generate three output pulses that being convert to beat first and two choice beat. Two elector is used to produce two choice beat with different rapidity but still in the range of normal human heartbeat. All system structure is integrated to microcontroller ATmega8535 that used as main system in this research. The result of this research is a heartbeat simulator implemented to baby sleeping bed. Sensor system in the simulator worked and success in function. System could produce beat first and choice beat favourably and constantly. However, the velocity of beat first and first choice beat is a little different to estimated where beat first velocity 2 second slower and first choice beat velocity 1 second slower. Baby respon to system at low velocity (70 beat/minute) is calmer but at higher velocity (90 beat/minute) baby looked uncomfortable.